2004
DOI: 10.1038/sj.ijo.0802739
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of healthy and desirable body size in urban Senegalese women

Abstract: OBJECTIVE: To examine the cultural ideals for body size held by urban Senegalese women; to determine the body size that women associate with health; and to estimate the change in prevalence of female obesity in an urban neighbourhood of Dakar. DESIGN: Cross-sectional, population-based study in the subject's home, using a structured interviewer-administered questionnaire, conducted in the same Dakar neighbourhood as that of a previous survey conducted in 1996. SUBJECTS: A total of 301 randomly selected women, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
140
2
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(157 citation statements)
references
References 23 publications
11
140
2
4
Order By: Relevance
“…It is interesting to observe that there were more overweight and obese subjects who did not feel overweight than overweight and obese subjects who did feel overweight. This is consistent with other studies showing a greater level of body satisfaction in African subjects (Loveloy, 2001;Wildes et al, 2001;Holdsworth et al, 2004). In spite of this we found that women tried to lose weight more often than men and it is even more noteworthy to observe that 22% of YW wanted to lose weight but only 14% had a BMI greater than 25 kg/m 2 .…”
Section: Urbanization and Obesity In The Gambiasupporting
confidence: 93%
“…It is interesting to observe that there were more overweight and obese subjects who did not feel overweight than overweight and obese subjects who did feel overweight. This is consistent with other studies showing a greater level of body satisfaction in African subjects (Loveloy, 2001;Wildes et al, 2001;Holdsworth et al, 2004). In spite of this we found that women tried to lose weight more often than men and it is even more noteworthy to observe that 22% of YW wanted to lose weight but only 14% had a BMI greater than 25 kg/m 2 .…”
Section: Urbanization and Obesity In The Gambiasupporting
confidence: 93%
“…Earlier studies have also shown higher incidence of obesity among females than males (Adebayo et al, 2014;Fadupin et al, 2014;Banwat et al, 2012;Wahab et al, 2011). The recurring higher prevalence of obesity among women have been linked to gradual weight gain with successive pregnancies, perception of weight gain as evidence of socio-economic class, fattening practices and sedentary lifestyle (Akarolo-Anthony et al, 2014;Holdsworth et al, 2004;Brink, 1989). The high incidence of abdominal obesity is worrisome following the reported links with liver fat accumulation and associated metabolic syndrome (Jakobsen et al, 2007;Haap et al, 2011), which could increase the existing burden on the Nigerian health system.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing prevalence of obesity in the developing world is compounded by the cultural view of obesity as being a positive attribute, signifying both health and wealth. This is particularly so in African nations, 9 and is in stark contrast to the Western ideal, as portrayed in the mass media, of thin is beautiful! Central adiposity, ectopic fat deposition and obesity-related co-morbidities 'Not all fat is created equal' may be the new dogma in obesity research, with many studies reporting that the pathological effects of excessive adiposity are dependent not only on the quantity of fat, but on the distribution of the fat mass.…”
Section: A Changing View Of Adiposity Through the Agesmentioning
confidence: 97%